Defining investment in a future WTO agreement on investment facilitation for development - Christian Pitschas (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2022)
The draft text for an Investment Facilitation for Development Agreement does not define the term "investment." If negotiators wish to define said term, they should take guidance from the WTO rule book. It characterizes trade-related investment as a business or professional establishment by a WTO member's person in another WTO member's territory for purposes of providing goods or services.
Keywords: 330